Extracts of Eucalyptus alba Promote Diabetic Wound Healing by Inhibiting α-Glucosidase and Stimulating Cell Proliferation. (15th April 2022) - Mumtaz, Rabia; Zubair, Muhammad; Khan, Muhammad Asaf; Muzammil, Saima; Siddique, Muhammad Hussnain
Abstract : Treatment of diabetic wounds has always been a challenge for primary and acute health care. Eucalyptus alba has been reported to be used for the treatment of wounds and oxidative stress. Effects of using different temperatures and solvents for the extraction of Eucalyptus alba leaves were investigated in terms of diabetic wound healing activity. Leaves of E. alba were dried at 10°C, 30°C, 50°C, and 100°C, and dissolved in ethanol, methanol, and acetone to obtain a total of 12 extracts. All the extracts have remarkable antidiabetic, antioxidant, and cell proliferation activities. Among the tested extracts, highest activities were observed with leaves dried at 10°C and 30°C, whereas drying at 100°C resulted in the lowest activities. Ethanol-based extracts exhibited significantly increased cell proliferation compared with methanol- and acetone-based extract. The present study suggests that leaves of E. alba should be dried at temperature not more than 30°C and extracted in ethanol for optimum results. However, further studies should focus on the identification of specific bioactive compounds in E. alba leaves.